What Can We Learn From International Student Performance Studies? Some Methodological Remarks - Michael Fertig (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2004)
The determinants which are decisive for a successful accumulation of human capital and the transfer of these skills into the labor market are a contentious issue in the literature on the economics of education. Different studies on, for instance, the impact of school resources typically reach different conclusions even if they utilize the same dataset. The reason behind this is that each and every study decisively depends on a set of identification assumptions which are anything but innocuous for the results obtained.This paper aims at clarifying this point by embedding the discussion on the determinants of test success in international performance studies like PISA into a theoretical model of cognitive achievement and an empirical frame of reference.
Keywords: I21; 330; PISA 2000; cognitive achievement; identification; Bildungsniveau; Bildungsertrag; Kognition; Theorie; Welt; PISA